THE PHENOMENON OF PICKING UP BALLS IN THE PPDB PROCESS (PHENOMENOLOGY STUDY OF PICKING UP FOOTBALL AT SMK SIANG 1 BOJONEGORO): FENOMENA PENJEMPUTAN BOLA DALAM PROSES PPDB (STUDI FENOMENOLOGI PENJEMPUTAN SEPAKBOLA SMK SIANG 1 BOJONEGORO) - Titin Sekartika (SOSIOEDUKASI, 2020)
Private educational institutions have various methods of recruiting students according to school needs. In general, these schools prefer to implement PPDB (New Student Admissions) with the "pick up ball" method, rather than taking PPDB Online. PPDB "pick the ball" is a method of recruiting students that is followed by all school units including, educators and students. They go directly to the field to find and pick up students. So, not only students who come to the school to register, but the school will pick up prospective students. This research is a qualitative study using the Alfred Schutz phenomenology approach. Max Weber's theory of social action as the analysis knife of this research. The focus of this research study is the SMK Siang 1 Bojonegoro school unit. The selection of informants was done purposively. Data obtained through observation, indepth interview, and documentation. The results of the study, SMK Siang 1 Bojonegoro has several reasons for "picking up the ball", including: maintaining school prestige, eliminating negative stereotypes, competition between schools, increasing economic capital, bureaucratic efficiency, and the existence of a communal culture in the Bojonegoro community. There are two strategies used to make "pick the ball" successful. Hegemony strategy, actors act on the basis of franchise principles, seen from the side of efficiency and effectiveness alone. Meanwhile, the actor's Social Capital strategy acts based on moral and religious values.